The new digital age: Reshaping people, nation and business through flipped arena (final empirical findings) - Omolara, Salisu Idayat; Auyphorn, Panadda; Habibullah, Md; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
Flipped Arena can be seen as communication technique that consists of two parts: interactive learning activities, and direct computer-based individual instruction outside the four walls. The aim of this study to look into the flip arena where people can learn, in many area, where the old or physically challenge people can be able gain knowledge and speak freely. On the other hand, introducing the rural area into the future. This research will provides an inclusive survey of respondence by students and people at different areas, data analysis and empirical findings. Moreover, the final conceptual solution model will be established based on business model canvas (BMC) and VPD.